A taxonomic review of the newly recorded genus Cyanotiphia Cameron, 1907 (Hymenoptera, Tiphiidae, Tiphiinae) from China, with a key to all known species - Feng, Ziyan; Chen, Bin; Li, Tingjing (Zootaxa, 2025)
In this study, the genus Cyanotiphia Cameron, 1907 of the subfamily Tiphiinae is newly recorded from China and reviewed. One new species named C. breviclypeola Feng, Chen & Li, sp. nov. from Chongqing (China) is described and illustrated in detail, and C. fenchihuensis (Tsuneki, 1986), comb. nov. (China: Taiwan and Guangdong) is transferred from Tiphia (Punctotiphia). An original key to all the known species of the genus is given.